2013
DOI: 10.1002/eji.201242570
|View full text |Cite
|
Sign up to set email alerts
|

Differential compartmentalization of memory B cells versus plasma cells in salmonid fish

Abstract: The disposition of teleost memory and plasma cells (PCs) has essentially been unexplored. As the organization of the teleost immune system differs significantly from that of mammals (i.e. no bone marrow or lymph nodes, hematopoietic anterior kidney), this disposition could be essential in understanding how comparable functions are achieved. To address this question, the primary and secondary antibody-secreting cell, B memory cell, and antibody responses to T-independent and T-dependent antigens were analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 57 publications
(143 reference statements)
1
39
4
Order By: Relevance
“…The relative similarity of the head kidney transcriptomes among vaccinated seabass compared to control seabass could hence be a consequence of the presence of a large mono-population of long-live plasma cells. This pattern of B cell differentiation, proliferation and migration was similarly observed in a study based on ELISPOT assays and carried out on rainbow trout ( Oncorhynchus mykiss ) subjected to an exposure of bacterial-based antigens [37]. Our result also implied that vaccinated seabass could still possibly be vulnerable to a bacterial infection shortly after vaccination (at least within one week) since long-lived plasma cells need some time to establish themselves in the head kidneys.…”
Section: Discussionsupporting
confidence: 84%
“…The relative similarity of the head kidney transcriptomes among vaccinated seabass compared to control seabass could hence be a consequence of the presence of a large mono-population of long-live plasma cells. This pattern of B cell differentiation, proliferation and migration was similarly observed in a study based on ELISPOT assays and carried out on rainbow trout ( Oncorhynchus mykiss ) subjected to an exposure of bacterial-based antigens [37]. Our result also implied that vaccinated seabass could still possibly be vulnerable to a bacterial infection shortly after vaccination (at least within one week) since long-lived plasma cells need some time to establish themselves in the head kidneys.…”
Section: Discussionsupporting
confidence: 84%
“…injection, it is currently unknown how the virus is transmitted under natural conditions (e.g., cohabitation with or ingestion of infected fish). Regardless of the route of infection (natural or by injection), it is clear that FHMNV can cause significant necrotic changes in hematopoietic tissues in multiple organs such as liver, kidneys, and spleen, a matter that may affect the ability of resident white blood cells to mount potent immune responses (Bromage et al 2004;Ma et al 2013). The studies of Iwanowicz and Goodwin (2002) described similar lesions in the liver, kidneys, and spleen of experimentally infected Fathead Minnows.…”
Section: Discussionmentioning
confidence: 99%
“…In salmonids, it has been established that memory B cells response occurs but in a much lesser degree in comparison to mammals. Antigenic re-stimulation of these cells promotes only arithmetic but not logarithmic increase of the antibody titers upon second challenge with thymus-dependent antigens (21). In the same line, our results showed that upon booster immunizations the antibody titers tend to increase arithmetically in comparison with the first immunization.…”
Section: Discussionmentioning
confidence: 99%